Gastroenteritis Attributable to 16 Enteropathogens in Children Attending Day Care: Significant Effects of Rotavirus, Norovirus, Astrovirus, Cryptosporidium and Giardia. Issue 1 (January 2015) - Enserink, Remko; van den Wijngaard, Cees; Bruijning-Verhagen, Patricia; van Asten, Liselotte; Mughini-Gras, Lapo; Duizer, Erwin; Kortbeek, Titia; Scholts, Rianne; Nagelkerke, Nico; Smit, Henriette A.; Kooistra-Smid, Mirjam; van Pelt, Wilfrid
Abstract : Background: Children attending day care experience substantial gastrointestinal morbidity due to circulating seasonal enteropathogens in the day-care environment. The lack of a distinct clinical presentation of gastroenteritis (GE) in these children, in combination with the high diversity of enteropathogenic agents, complicates the assessment of the individual contributions of enteropathogens that may cause GE. We aimed to estimate the proportion of day-care attendees experiencing GE that could be attributed to a range of enteropathogens circulating in day care in the Netherlands in 2010–2013. Methods: Using time-series data from a national laboratory-based and syndrome-based surveillance system in Dutch day-care centers and generalized estimating equation analysis, we modelled the variation in prevalence of 16 enteropathogens of bacterial (8), viral (5) and parasitic origin (3) circulating in day care to the variation of GE incidence among children attending day care. Results: Rotavirus, norovirus, astrovirus, Giardia and Cryptosporidium were significantly associated with GE morbidity among day-care attendees in our time-series analysis. Together, these enteropathogens accounted for 39% of the GE morbidity: 11% by rotavirus, 10% by norovirus, 8% by Giardia, 7% by astrovirus and 3% by Cryptosporidium . Conclusions: We demonstrate that circulating viruses and parasites, rather than bacteria, contribute to seasonal GE experienced by children in day care.